Enhanced antitumor activity of erlotinib in combination with the Hsp90 inhibitor CH5164840 against non‐small‐cell lung cancer. Issue 10 (20th August 2013) - Ono, Naomi; Yamazaki, Toshikazu; Tsukaguchi, Toshiyuki; Fujii, Toshihiko; Sakata, Kiyoaki; Suda, Atsushi; Tsukuda, Takuo; Mio, Toshiyuki; Ishii, Nobuya; Kondoh, Osamu; Aoki, Yuko
<x xml:space="preserve">Abstract</x> Inhibition of heat shock protein 90 (Hsp90) can lead to degradation of multiple client proteins, which are involved in tumor progression. Epidermal growth factor receptor (EGFR) is one of the most potent oncogenic client proteins of Hsp90. Targeted inhibition of EGFR has shown clinical efficacy in the treatment of patients with non‐small‐cell lung cancer (NSCLC). However, primary and acquired resistance to the existing EGFR inhibitors is a major clinical problem. In the present study, we investigated the effect of the novel Hsp90 inhibitor CH5164840 on the antitumor activity of erlotinib. The NSCLC cell lines and xenograft models were treated with CH5164840 and erlotinib to examine their mechanisms of action and cell growth inhibition. We found that CH5164840 showed remarkable antitumor activity against NSCLC cell lines and xenograft models. The addition of CH5164840 enhanced the antitumor activity of erlotinib against NCI‐H292 EGFR‐overexpressing xenograft models. Phosphorylation of Stat3 increased with erlotinib treatment in NCI‐H292 cells, which was abrogated by Hsp90 inhibition. Furthermore, in a NCI‐H1975 T790M mutation erlotinib‐resistant model, CH5164840 enhanced the antitumor activity of erlotinib despite the low efficacy of erlotinib treatment alone. In addition, ERK signaling was effectively suppressed by combination treatment with erlotinib and CH5164840 in a NCI‐H1975 erlotinib‐resistant model. Taken together, these data indicate that CH5164840 has potent antitumor activity and is highly effective in combination with erlotinib against NSCLC tumors with EGFR overexpression and mutations. Our results support the therapeutic potential of CH5164840 as a Hsp90 inhibitor for combination therapy with EGFR‐targeting agents against EGFR‐addicted NSCLC.